2004
DOI: 10.1016/j.euje.2004.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic classification of chronic ischemic mitral regurgitation caused by restricted motion according to tethering pattern

Abstract: Although the mechanism of ischemic mitral regurgitation (MR) is understood, the echocardiographic picture of ischemic MR is not homogeneous. Ninety-two consecutive patients with chronic ischemic MR due to restricted motion were divided into two groups according to tethering pattern: the asymmetric group with predominant posterior tethering of both leaflets (54 patients) and the symmetric one with predominant apical tethering of both leaflets (38 patients). The mitral deformation indexes, LV global (volume, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
0
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 30 publications
7
127
0
12
Order By: Relevance
“…1-5 Therefore, leaflet tethering can be heterogeneous according to the variability of the components of the MV complex. As one such case of heterogeneous tethering, differing degrees of anterior and posterior mitral leaflet (AML and PML) tethering have been reported, 6 but the corresponding mechanism has not been fully investigated.…”
mentioning
confidence: 99%
“…1-5 Therefore, leaflet tethering can be heterogeneous according to the variability of the components of the MV complex. As one such case of heterogeneous tethering, differing degrees of anterior and posterior mitral leaflet (AML and PML) tethering have been reported, 6 but the corresponding mechanism has not been fully investigated.…”
mentioning
confidence: 99%
“…In our series, the MR jet direction was mainly posterior before surgery (72%) but rarely posterior after annuloplasty (20%). Consistently, Agricola et al (11) reported that the preoperative jet direction was posterior in the vast majority (83%) of their patients with ischemic MR. On the other hand, Zhu et al (6) reported that in a subset of patients (n=6) with persistent MR after surgery, postoperative MR jet direction was most frequently anterior (n=2) or central (n=4).…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, eccentric MR can also be quantified by measuring vena contracta width, and Lesniak-Sobelga et al (13) have shown excellent correlation between vena contracta width and effective regurgitant orifice area, regurgitant volume and regurgitant fraction. Several echocardiographic studies have provided new insights into the mechanisms of ischemic MR (6,11). The basic mechanism of ischemic MR is leaflet tethering by the outward displacement of papillary muscles due to LV remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of tension exerted on the leaflets mainly depends on the entity of PMs displacement, which is the actual cause of the impaired coaptation and valve regurgitation observed in IMR. Tethering can have a symmetric or asymmetric pattern reflecting the direction of PM displacement vector, the localization of myocardial infarction zone and the severity of global ventricular dysfunction (15,16). Normally PMs provide a number of chordae that are attached to both leaflets, anterior and posterior, but with a substantial difference in case of symmetric or asymmetric tethering shape.…”
Section: Diagnosis and Considerations Of Geometric Parameters Conditimentioning
confidence: 99%